A novel HIF-1α/VMP1-Autophagic Pathway Induces Resistance to Photodynamic Therapy in Colon Cancer Cells. - Rodriguez, Matias Exequiel (2017)
Colon cancer is the third most frequent cancer and the fourth most common cause of cancer-related mortality worldwide and the standard therapy is surgical resection plus adjuvant chemotherapy. Photodynamic therapy (PDT) has been proposed as adjuvant therapy because it can prevent the tumor recurrence after surgical excision in colon cancer patients. Hypoxia is a common feature in solid tumor and leads to chemo/radio resistance. Recently, it has been shown that in response to hypoxia cell can induce HIF-1α-mediated autophagy to survive in this hostile microenvironment. Moreover, hypoxia and autophagy have been implicated in resistance to antitumor PDT. However, the molecular signals by which HIF-1α induces autophagy in PDT context has not been studied yet. Here we evaluate theinterplay between HIF-1α and autophagy as well as the underlying mechanism in the PDT resistance of colon cancer cells. Our study demonstrates that HIF-1α stabilization significantly increases VMP1-related autophagy through binding to hypoxia responsive elements in VMP1 promoter. We show that HIF-1α-induced utophagy increases colon cancer cell survival as well as decreses cell death after PDT. Moreover, here we demonstrate that HIF-1α-induced autophagy is mediated by VMP1 expression, since downregulation of VMP1 by RNA interference strategy reduces HIF-1α-induced autophagy and cell survival after PDT. In conclusion, PDT induces autophagy as a survival mechanism and the induction of the novel HIF-1α/VMP1/autophagic pathway may explain, at least in part, theresistance of colon cancer cells to PDT. The knowledge of the molecular mechanisms involved in PDT resistance may lead to more accurate therapeutic strategies.